Investigación y formación de recursos humanos en ciencias sociales sobre la Amazonia - ARAGÓN VACA, Luis Eduardo (2012)
This is a study of the state of the art of the scientific research in social sciences in continental Amazonia. The study concludes that it is extremely difficult to define the situation of scientific research in social science with the data available for the study. Nevertheless the study was able to identify some 150 institutions that conduct research and produce science and technology related to the Amazon in the eight countries, of which approximately 100 conduct research on social sciences. Those institutions are located mainly in Brazil and Colombia.